Antimicrobial potential of Satureja montana agroindustrial byproducts as possible ingredients in animal feed - Santos, Jéssica Daniela Carvalho dos (2018)
Phytobiotics and prebiotics have been investigated as natural alternatives to antibiotic growth promoters (AGPs) in poultry industry. The present work evaluated antimicrobial activity of agroindustrial Satureja montana byproducts and the presence of potential prebiotic molecules in Allium cepa byproducts as possible ingredients in broiler diets. Essential oils (EOs) were obtained from Satureja montana branches by hydrodistillation (≈120 min) with convective heating, and by microwave assisted hydrodistillation (16±1 min) of rehydrated and drained branches, obtaining similar yields of 0.14±0.07 and 0.10±0.01 mg/g, respectively. GC-MS analysis revealed that the EOs obtained by different extraction methodologies and harvest had similar chemical composition. A total of 13 compounds were identified. Monoterpenoids account for 84.4 – 97.6% and sequiterpenoids 0.3 – 0.5%, being carvacrol the highest component (825 – 950 μg/mg). Antimicrobial activity of essential oils was individually evaluated against Escherichia coli ATCC 25922, Salmonella enterica sv Anatum SF2 and Staphylococcus aureus ATCC 6538 using an agar disc diffusion method and broth microdillution assay. All tested microorganisms were inhibited by EO obtained from byproducts of the Satureja montana. Gram-negative bacteria strains (E. coli 25922 and Salmonella SF2) were much less susceptible than Gram-positive bacteria (S. aureus 6538) to the tested EO. The activity of tested EO is related to the presence of high levels of carvacrol, obtaining minimal inhibitory concentration (225 for E. coli 25922, 250 for Salmonella SF2, and 150 μg/mL for S. aureus 6538) similar to carvacrol in same strains. Onion byproducts extracts were obtained by sequential extraction with boiling ethanol:water (8:2) and water at 80°C. In comparison, microwave superheat water and ethanol:water (65:35) extracts were obtained at 120, 140, and 160°. Carbohydrate composition and glycosidic linkage analysis revealed that the presence of pectic polysaccharides and terminally-linked glucose probably from glycoconjugated phenolic compounds. Within the detected oligosaccharides, all extracts showed only disaccharides (namely sucrose and trehalose) in an amount of less than 7 μg / mg. However, prebiotics such as inulin and fructooligosaccharides could be diagnostic by (1→2)-linked fructose in the onion byproducts at low amounts. The soluble fiber from onion byproducts have potential to be exploited as prebiotics. It is concluded that the Satureja montana byproducts have an antimicrobial potential against the main pathogenic bacteria of the birds becoming promising as an alternative in the substitution / reduction of the antibiotics in the feeds